E-Commerce Success Factors: PLS-SEM Approach - Muntaha Muntaha (AIBPM Publisher, 2022)
The current research gap on e-commerce is still relatively incomplete, with predictors in the research model still relatively weak in influence. The purpose of this research is to empirically test the role of the 'satisfaction' variable, whether it is able to fully mediate the relationship between predictors and e-commerce success variables. This research chose the location in the province of West Kalimantan, on the grounds that this province is one of three provinces in Indonesia which has a direct land border with a neighboring country (Malaysia). This research uses the WarpPLS 7.0 analysis tool, arguing that this research is more focused on exploring the 'satisfaction' variable which functions as a mediating variable to 'try' to cover the gaps of previous research. The results of this study found that the satisfaction variable has a significant influence in mediating the relationship between Website service quality, Customer Support System, Electronic Word of mouth and Personalization on E-Commerce success in MSMEs in West Kalimantan province. Consumer satisfaction in being an important factor for business managers, consumers who have high satisfaction will have a positive impact on MSMEs, so that the potential to increase sales turnover becomes bigger and better.